2020
DOI: 10.14701/ahbps.2020.24.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of COL6A3 in pancreatic adenocarcinoma

Abstract: Backgrounds/Aims: Pancreatic cancer is one of the most fatal human malignancies with poor prognosis, despite advances in therapy. Here, we evaluated the potential role of collagen type VI 3 chain (COL6A3) as a non-invasive biomarker for pancreatic adenocarcinoma. Methods: In this study, we investigated immunohistochemically the expression of COL6A3 in 30 patients with resectable pancreatic adenocarcinoma by immunohistochemistry in a tissue sample of the cancer and a tissue sample of normal pancreas for each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…3), encoding the α-3 chain of type VI collagen, which has been found to participate in the tumor malignant processes in gastric, pancreatic, and ovarian cancer [14]. So we hypothesized that circCOL6A3_030 also played an important role in the malignant progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 97%
“…3), encoding the α-3 chain of type VI collagen, which has been found to participate in the tumor malignant processes in gastric, pancreatic, and ovarian cancer [14]. So we hypothesized that circCOL6A3_030 also played an important role in the malignant progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Svoronos et al. ( 54 ) showed that in the PDAC stroma, COL6A3 is the major overexpressed gene, and overexpressed COL6A3 leads to a poor prognosis in PDAC. Arafat et al.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence had demonstrated COL6A1-3's role in promoting the progression of tumors [37]. COL6A2 was dysregulated and associated with poor prognosis by involving in TGFβ1 pathway in serous ovarian cancer [38,39]. COL6A3 may take part in the tumorigenesis and progression of cholangiocarcinoma through E2F1/LMCD1-AS1/miR-345-5p/COL6A3 axis and might act as a prognostic factor for pancreatic cancer [40].…”
Section: Discussionmentioning
confidence: 99%